(NfORTEPXQNNOE NASLEDIE ~AJKOWSKOGOs (NMONOGRAFIQs - (Na (B.(NnIKOLAEWs ((NmOSKWAs (NmUZYKIs, 1958)
(NnASTOQ]AQ RABOTA (B,(NPOSWQ]ENNAQ FORTEPXQNNOMU NASLEDI@ p(B.(Ni(B.(N~AJKOWSKOGO (B,(NADRESOWANA [IROKOMU KRUGU ^ITATELEJ(B.s
Keywords: (NmONOGRAFIQs